2011
DOI: 10.1016/j.ahj.2010.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smoking and smoking cessation on lipids and lipoproteins: Outcomes from a randomized clinical trial

Abstract: Background The effects of smoking and smoking cessation on lipoproteins have not been studied in a large contemporary group of smokers. This study was designed to determine the effects of smoking cessation on lipoproteins. Methods One-year, prospective, double-blind, randomized, placebo-controlled clinical trial of the effects of 5 smoking cessation pharmacotherapies. Fasting nuclear magnetic resonance spectroscopy lipoprotein profiles were obtained before and 1-year after the target smoking cessation date. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
132
3
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(152 citation statements)
references
References 35 publications
(57 reference statements)
9
132
3
8
Order By: Relevance
“…Smoking is associated with a more atherogenic lipid profile [3][4][5]. It increases the concentration of serum total Cholesterol, triglycerides, LDLCholesterol, VLDL-Cholesterol and decreases the level of good Cholesterol i.e., HDL-Cholesterol [6][7][8][9][10]. Thus, smoking is a major risk factor for atherosclerosis and coronary artery disease [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Smoking is associated with a more atherogenic lipid profile [3][4][5]. It increases the concentration of serum total Cholesterol, triglycerides, LDLCholesterol, VLDL-Cholesterol and decreases the level of good Cholesterol i.e., HDL-Cholesterol [6][7][8][9][10]. Thus, smoking is a major risk factor for atherosclerosis and coronary artery disease [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Smoking cessation has been known to result in an improvement in lipid profile, as reflected in enhanced levels of HDL, 31) and a rapid decline in cardiovascular risk. 32) Following smoking cessation, coronary endothelial vasomotor abnormality recovers in healthy young smokers, 33) although not in middle-aged smokers or long-term smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Impact of smoking on coronary physiology: The finding that among patients with CAD, smokers had greater IMR than nonsmokers, suggests that smoking adversely affects coronary microcirculatory resistance. Smoking is associated with coronary endothelial dysfunction, 23) coronary vascular smooth muscle relaxation, 24) dyslipidemia, 25,26) progression of coronary atherosclerosis, 27) and cardiovascular events. 28) Although the mechanisms of CMVD associated specifically with smoking have not been fully established, CMVD with CAD is caused in general by two mechanisms: inappropriate subepicardial prearteriolar dilatation in the presence of increased myocardial oxygen consumption, and prearteriolar and arteriolar constriction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the current study indicated that past smoking is associated with dyslipidemia and hypertriglyceridemia in men. Cessation of smoking is reported to have relatively limited effects on lipid profiles (24,25). A meta-analysis showed that smoking cessation led to increased serum concentration of HDL-cholesterol, but no significant improvement in serum triglycerides and LDL-cholesterol (25).…”
Section: Discussionmentioning
confidence: 99%